Long-term outcomes of adults with first-relapsed/refractory systemic anaplastic large-cell lymphoma in the pre-brentuximab vedotin era: A LYSA/SFGM-TC study. (September 2017) - Morel, Alexandre; Brière, Josette; Lamant, Laurence; Loschi, Michaël; Haioun, Corinne; Delarue, Richard; Tournilhac, Olivier; Bachy, Emmanuel; Sonet, Anne; Amorim, Sandy; Laurent, Camille; Gaulard, Philippe; et al.
Abstract: Background: Long-term outcomes of adults with first-relapsed/refractory (R/R) systemic anaplastic large-cell lymphoma (ALCL) are not definitively established and should be evaluated. Patients and methods: We previously published the long-term outcomes of adults with ALCL initially treated with polychemotherapy in LYmphoma Study Association (LYSA) prospective clinical trials conducted during the pre-brentuximab vedotin era. Herein, we report the long-term outcomes of those patients after the first-relapsed/refractory (R/R) events. Results: Among the 138 (64 (anaplastic lymphoma kinase (ALK(+)) and 74 ALK(−) ALCL) adults initially treated in clinical trials, 40 (14 ALK(+) and 26 ALK(−)) first-R/R ALCL patients and their long-term outcomes were analysed. Median follow-up from the first-R/R events was 12.5 years. For ALK(+) and ALK(−) patients, respectively, median [range] findings were as follows: age at first-R/R event: 35 [19–76] and 61 [34–81] years; time between inclusion in first-line clinical trials and first-R/R events was 6 [1.5–34] and 11.1 [1–67] months (P = 0.36); with median (95% confidence interval) progression-free survival after the first-R/R events: 3.8 (0.7–14.8) and 5.3 (2.4–8.4) months (P = 0.39); and overall survival: 13.6 (0.7–89) and 8.1 (3.3–25) months (P = 0.96). ALCL was the main cause of death. Conclusion: Most adults with first-R/R ALCL have poor outcomes, with no significant differences between patients with ALK(+) or ALK(−) disease. These results could be used as reference for the evaluation of new drugs to treat R/R ALCL. Highlights: Long-term outcomes of adults with first-relapsed/refractory ALCL in the pre-brentuximab vedotin era are described. Most adults with first-relapsed/refractory ALCL have poor outcomes. Survival of ALK(+) and ALK(−) patients did not differ.